APTITUDE AND PERSONALITY TESTING: WHAT DOES MEDICAL AND DENTAL COLLEGES ENTRANCE TEST 2012 ADD TO THE DEBATE? - Junaid Sarfraz Khan; Osama Mukhtar et al. (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To determine the relationship amongst the premedical academic achievement, aptitude test and the Entrance Test in the Punjab Medical & Dental Colleges admission test 2012. Methodology: An aptitude test of 22 items was administered to the entire population of Entrance Test 2012. HSSC, Matriculation, aptitude test, and Entrance Test scores and their demographic variables were entered into Statistical Package for Social Sciences (SPSS) software v.16 and parametric tests were applied. P-value less than 0.05 was as taken as statistically significant. Results: Out of the 36,100 students, 24,988 (69.2%) were females. Students who scored more than 75% marks (19.9%) also scored higher marks in the Aptitude Test (t=28.45. p-value=0.00). Female candidates in general scored higher marks in the Entrance Test (p<0.05) and in the Aptitude Test (p>0.05). Overall, students from the economically and academically underdeveloped districts of Punjab scored less marks in the Entrance Test (p<0.05) and the Aptitude Test (p<0.05). The difference in Entrance Test and Aptitude Test marks of students from underdeveloped districts was greater than that of students for the developed districts (p<0.05). However, in Matriculation and Intermediate examinations, students from the underdeveloped districts scored higher marks than the developed districts (p<0.05). Students scoring higher marks in Matric and Intermediate, scored low marks in the Aptitude Test (p <0.05). Conclusion: In Pakistan aptitude, personality and cognitive testing will need to be combined in just the right way to select candidates for admission in health professional education program that can contribute effectively in delivering preventive and primary healthcare services to the large majority of the population deprived of the same for past 65 years.